alpha-SiAlON ceramics with elongated grain morphology using an alternative sintering additive - Santos, C.; Strecker, K.; Ribeiro, S.; de Souza, JVC; Silva, OMM; da Silva, CRM (Elsevier B.V., 2004)
In this work, the use of a natural yttrium oxide and rare earth oxide solid solution (CRE2O3) as stabilizers of the alpha-Si3N4 phase to form alpha-SiAlON has been investigated. This oxide mix is produced at FAENQUIL-DEMAR, at a cost of only 20% of pure commercial Y2O3. Two alpha-SiAlONs using pure Y2O3 or CRE2O3 have been prepared, using mixes of 20% by volume of a molar fraction of 9:1 of AlN to Y2O3 or AlN to CRE2O3, respectively, with 80% alpha-Si3N4. Samples were gas pressure-sintered at 1900 degreesC, under 1.5 MPa of N-2 for 60 min. Both compositions yielded alpha-SiAlON ceramics with high relative densities (98% t.d.), hardness of 18 GPa and fracture toughness of 5 Mpa m(1/2), with homogeneous microstructures composed of elongated alpha-SiAlON grains with aspect ratios of 5. It is concluded that the mixed rare earth concentrate (CRE2O3) can be used to produce alpha-SiAlON ceramics with similar microstructures and mechanical properties of alpha-SiAlON ceramics fabricated using pure Y2O3, but with the advantage of its lower production cost. (C) 2004 Elsevier B.V All rights reserved.
Keywords: sintering additive; alpha-SiAlON; microstructure; mechanical properties